FREQUENCY OF VISCERAL LEISHMANIASIS IN ABBOTTABAD FROM 2005 TO 2009 - Nadeem, Seema; Shamroz, Sabah; Iqbal, Touqueer; Manan, Modood ul; Salaam, Abdus (Journal of Ayub Medical College Abbottabad, 2010)
Background: Leishmaniasis is a parasitic disease caused by a haemoflagellate Leishmania, transmitted to humans through bites of female sand fly. The objective of this study was to assess the frequency of leishmaniasis in Abbottabad and nearby areas including villages of Nawanshehr, Dhodial, Gamavan, Sheikhulbandi, Kakul and Malikpura. Method: This was a retrospective study carried out in Pathology Department, Women Medical College and Benazir Bhutto Teaching Hospital Abbottabad from 2005 to 2009. The diagnosis was based on intracellular and extracellular amastigote forms of Leishmania donovani in the bone marrow aspirates. Results: We diagnosed 61 cases of visceral leishmaniasis, mostly from Nawanshehr (32.78%), in children below 5 years of age with febrile splenomegaly. Conclusion: The disease is gradually spreading southwards in the country. A high index of suspicion should be kept in mind for all cases coming from Northern Areas of the country where the frequency is quite high. Local health authorities should take drastic action against this spreading disease. Keywords: visceral leishmaniasis, bone marrow, leishmaniasis